Complete response of unresectable icteric-type hepatocellular carcinoma to hypofractionated proton beam therapy with concurrent plus adjuvant sorafenib: a case report - Hsieh, Cheng-En; Hong, Ji-Hong; Lin, Chen-Chun; Lee, Ching-Hsin; Hung, Sheng-Ping; Chou, Chen-Yu; Chen, Chien-Ming; Tseng, Jeng-Hwei (Therapeutic Radiology and Oncology, 2018)
Icteric-type hepatocellular carcinoma (HCC) is a rare entity of liver malignancy, characterized by direct tumor invasion into biliary system. En bloc resection of the tumor has long been the only treatment of choice conferring long-term survival. Cure through non-surgical approaches remains anecdotal. We present a 68-year-old male patient with a pathologically-proven unresectable icteric-type HCC obstructing the common hepatic duct and segmental portal veins. High-dose hypofractionated proton beam therapy (PBT) for 72.6 GyE in 22 fractions plus concurrent and adjuvant sorafenib was administered. After PBT completion, his total bilirubin levels and liver function tests gradually normalized, and the Child-Pugh score remained 5 (category A). Post-PBT 1-year MRI documented a complete response of tumor in accordance with the modified Response Evaluation Criteria in Solid Tumors (mRECIST) guideline, dissipation of vasculobiliary thrombi, and regression of biliary tract dilatation. After a follow-up of 27 months, the patient remained alive without evidence of recurrence. This successful treatment response with minimal hepatic toxicity suggests PBT may be a promising modality in the definitive management of unresectable icteric-type HCC.